THE REUSABLE COFFEE CUP SYSTEM “BILLIE CUP” IN A UNIVERSITY SETTING: A PILOT-STUDY - DURAK Koray; DUQUE JIMENEZI Diana Raquel; KARADAVUT Berkay (Management of Sustainable Development)
500 billion disposable cups are consumed every year and contribute to polluting the natural environment. Reusable cups offer a reasonable alternative, especially in work or study places with efficient and sustainable washing facilities. In one coffee bar at a university building, disposable cups were completely banished and a reusable polypropylene cup, the so-called “Billie Cup”, was introduced together with automated deposit and washing facilities. Quantitative and qualitative analyses were performed to measure financial differences, waste reduction, and customer opinion. After introduction of the Billie Cup, we reduced approximately 2.5 kg of waste per week and did not report significant changes in weekly sales [median: 336 (interquartile range: 291–359) vs. 337 (297–349) drinks, respectively, P=1.000] or revenue [578 (492–612) vs. 576 (492–586) euro, respectively, P=0.833]. Furthermore, we reported significantly higher numbers of refilling a cup with a median of 21 (16–25) vs. 43 (38–59) drinks per week, respectively, P=0.017. Resulting from our questionnaires, we found that all respondents believed that disposable cups produce unnecessary waste on campus. Our pilot study demonstrates that a reusable coffee cup system along with banishing all disposable cups can be successfully implemented without decreasing monthly revenue or sales.